Suing for Peace at Any Cost?: Reading the Parable of the Two Kings (Luke 14.31–2) in Times of War - Zamfir, Korinna (New Testament studies, 2024)
The paper re-examines the parable of the king pondering about engaging in war with a more powerful enemy (Luke 14.31-2), focusing on questions commonly asked in antiquity and still relevant today with respect to war and suing for peace. These regard the cause of the war and the reasons for fighting, the tension between bravery and wisdom, the circumstances that may contribute to the defeat of a superior army and the costs of peace making. I explore this parable in the context of other Lukan passages touching on the topic of war and peace. I challenge the assumption that Luke was a pacifist, and I argue that the parable cannot provide answers to contemporary questions about the ethics of peace and war.